Pendidikan sebagai pilar utama pembangunan bangsa: Tantangan dan solusi di Indonesia - Ramadhani, Filiza Alyedia (Maliki Interdisciplinary Journal, 2024)
Education is an important foundation in the development of a nation. This article explores various aspects of education in Indonesia, starting from the role and importance of education in society, the challenges faced by the education system, to innovative solutions to improve the quality of education. Through literature review and analysis, this article aims to provide comprehensive insight into how education can contribute effectively to the development of individuals and society as a whole.